The predicate-argument-structures in the common German-Danish word-formation-patterns and their use in Danish-teaching - Stopyra, Janusz (Glottodidactica, 2014)
In this paper, the author tries to deliver exercises for Polish students of German language with Danish as other foreign language. On the basis of the common German-Danish word-formation-patterns, the author attempts to build a new Danish-learning-model, based on these common patterns, the parallelism of which stays on the level of ca. 60-95%, allowing so a more often German-Danish transfer. Using these and other similarities between the two languages a student of Danish with German as source language can from the very beginning learn Danish in a more effective way.